Beyond Barriers: Redefining Organ-on-Chip Architecture Through Emerging Designs - Olaizola Rodrigo, Claudia; Bayona, Clara; Randelovic, Teodora; Sharko, Vira; Monge, Rosa; Oliván, Sara (Jornada de Jóvenes Investigadores del I3A, 2025)
This study presents four barrier-free organ-on-chip devices using xurography, thermal bonding, and surface treatment for hydrogel confinement. Removing physical barriers enhanced cellular interaction. Devices were tailored for hypoxia, tumor invasion, immune response, and interstitial flow models, demonstrating a versatile, modular approach for physiologically relevant in vitro systems.